A Comparison between Effects of Theater-Based Art Therapy and Solution-Focused Therapy on Social Adjustment in Students with Low Academic Achievement - Tabatabaee Salehi, Behnoush; Dortaj, Fariborz; Sadeghi, Jamal; Akbarnattaj Shob, Nabiollah; Mohammadzadeh Edmellaee, Rajabali (Iranian Journal of Neurodevelopmental Disorders, 2024)
Objective: This study aimed to compare the effects of theater-based art therapy (TRT) and solution-focused therapy (SFT) on social adjustment in students with low academic achievement. Methods and Materials: A quasi-experimental methodology with a pretest/posttest design and an unmatched control group was adopted. The statistical population consisted of female students of lower-secondary high schools in grade 9 with low academic achievement (GPA<15) in Districts 5 and 7 of Tehran Municipality during the academic year of 2022-2023. Forty-five students meeting the inclusion criteria were selected as the participants via convenience sampling. They were randomly divided into two experimental groups and a control group (fifteen students in each group). The data were collected via the Weinberger Adjustment Inventory (WAI). In addition, the participants in the experimental groups attended ten 60-minute sessions of a TRT intervention designed according to Jones (1997) and eight 60-minute sessions of an SFT intervention designed according to Grant (2011); the control group received no intervention. The data were analyzed statistically using the repeated measures analysis of variance (ANOVA) in SPSS V.18. Findings: The results showed that both TRT and SFT had positive effects on the social adjustment of the participants; however, SFT was more effective than TRT. Conclusion: TRT can help adolescents improve their social adjustment and perform better in both daily life and education over time by using consistent, intentional exercises and activities. The TRT intervention can be customized to meet adolescents’ requirements.